1996
DOI: 10.1007/s004210050103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maximal arm exercise on skin blood flux in the paralyzed lower limbs in persons with spinal cord injury

Abstract: The purpose of the present study was to examine the effect of maximal arm exercise on the skin blood circulation of the paralyzed lower limbs in persons with spinal cord injury (PSCI). Eight male PSCI with complete lesions located between T3 and L1 performed graded maximal arm-cranking exercise (MACE) to exhaustion. The skin blood flux at the thigh (SBFT) and that at the calf (SBFC) were monitored using laser-Doppler flowmeter at rest and for 15 s immediately after the MACE. The subject's mean peak oxygen upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…One study reported a minimal increase in SCI and able-bodied individuals in femoral artery blood flow, 7 whereas, others reported a small decrease in calf volume 5 or no changes in cutaneous and femoral artery blood flow in SCI. 6,8 In agreement with those reports showing unchanged blood flow in lower limbs of SCI and able-bodied individuals during ACE, we document no effect of ACE at the level of muscle microcirculation. It appears that moderateintensity aerobic exercise involving relatively small muscle mass does not induce a systemic hyperemic response.…”
Section: Muscle Perfusion During Arm Exercisesupporting
confidence: 92%
See 1 more Smart Citation
“…One study reported a minimal increase in SCI and able-bodied individuals in femoral artery blood flow, 7 whereas, others reported a small decrease in calf volume 5 or no changes in cutaneous and femoral artery blood flow in SCI. 6,8 In agreement with those reports showing unchanged blood flow in lower limbs of SCI and able-bodied individuals during ACE, we document no effect of ACE at the level of muscle microcirculation. It appears that moderateintensity aerobic exercise involving relatively small muscle mass does not induce a systemic hyperemic response.…”
Section: Muscle Perfusion During Arm Exercisesupporting
confidence: 92%
“…4 Thus, the potential of ACE to enhance blood flow to non-exercising muscles, seems as an attractive intervention to increase the arteriole/capillary diameter, elicit capillarization and diminish the microvascular maladaptations in the paralyzed legs of SCI. The few studies that examined the effects of ACE on leg circulation in SCI have focused only on changes in limb volume, 5 cutaneous microcirculation, 6 and femoral artery blood flow 7,8 and reported equivocal results. Changes in limb volume and conduit artery blood flow, however, may not entirely reflect changes in muscle perfusion, and the blood flow response between the conduit artery and the microvasculature may vary substantially.…”
Section: Introductionmentioning
confidence: 99%
“…However, sweating response in a paraplegic is injured basically according to the level of the SCI Normell, 1974;Silver et al, 1991;Tam et al, 1978). Furthermore, SBFT which can be regarded as an index of vasodilation in the thigh is also affected by the level of the SCI (Cooper et al, 1957;Freund et al, 1984;Muraki et al, 1995;1996a, 1996b. Especially in paraplegics with high lesions, who have impaired sympathetic vasomotor function in the lower limbs, it has been suggested that skin blood flow is unchanged by exposure to a high temperature (Cooper et al, 1957;Guttmann et al, 1958;Yamasaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…During submaximal exercise (Muraki et al, 1995(Muraki et al, , 1996b and even maximal exercise (Muraki et al, 1996a), no increase in skin blood flow of the thigh (SBFT) was found in paraplegics with lesions at or above Th12 irrespective of the exercise intensity. However, SBFT in paraplegics with lesions below L1 increased proportionally with the increase in exercise intensity, if the tympanic membrane temperature (Tty) exceeded a threshold temperature of 36.69°C (Muraki et al, 1996b).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there is evidence for improved cutaneous and muscle microvascular perfusion responses to acute bouts of exercise in persons SCI (Muraki et al . , ; Theisen et al . ; Van Duijnhoven et al .…”
Section: Discussionmentioning
confidence: 99%